Nurses’ Knowledge, Attitudes, and Behavior in Solid Medical Waste Segregation at Klungkung Hospital - I Ketut Gede Samudra; I Gede Astra Wesnawa; I Ketut Sudiana; M. Choirul Hadi (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2026)
Improper segregation of solid medical waste in hospitals increases the risk of occupational injuries, nosocomial infections, and environmental pollution. Nurses play a key role in waste segregation, particularly in inpatient wards where medical waste is generated intensively. This study aimed to analyze the relationship between knowledge and attitudes with nurses’ behavior in solid medical waste segregation in inpatient wards at Klungkung District General Hospital. A quantitative cross-sectional study was conducted from January to June 2024 involving 71 nurses selected using proportional non-probability sampling. Data were collected using structured questionnaires to assess knowledge and attitudes, and observation checklists to assess behavior. Data were analyzed using Chi-square tests and contingency coefficients. Most nurses had good knowledge (67.6%), positive attitudes (80.3%), and good segregation behavior (78.9%). Significant relationships were found between knowledge and attitude (p < 0.001), knowledge and behavior (p < 0.001), and attitude and behavior (p < 0.001). Additional descriptive findings indicated that lack of understanding and time constraints hindered proper segregation, while awareness of health hazards, personal responsibility, and sanctions encouraged compliance. Nurses’ knowledge and attitudes were significantly associated with their behavior in solid medical waste segregation. Strengthening education, improving facilities, and consistent supervision are essential to enhance sustainable waste segregation practices in hospitals.